Enhanced expression of genes involved in coagulation and fibrinolysis in murine arthritis - Salvi, Roberto (BioMed Central, 2000)
INTRODUCTION: Accumulation of fibrin in the joints remains one of the most striking histopathological features of rheumatoid arthritis (RA). Recently, we have provided evidence of the deleterious role of synovial fibrin deposition in arthritic joints in antigen-induced arthritis (AIA), a well-established murine model of RA. A local imbalance between fibrin formation and fibrin dissolution may result in fibrin deposition in the joints. On the one hand, fibrin formation is mainly initiated by tissue factor (TF), a transmembrane protein serving as a receptor for factor VII. Under normal conditions, TF expression and activity are tightly regulated. Constitutive TF expression is restricted to perivascular and epithelial cells, and the catalytic activity of the TF/VIIa complex can be inhibited by tissue factor pathway inhibitor (TFPI). Pathological conditions can perturb the cell-type-restricted pattern of TF expression. In particular, recent reports have shown that transcriptional activation of TF can be mediated by molecular mechanisms involving induction of the early growth response gene 1 (EGR1) or of the protease-activated receptor (PAR1) or vascular endothelial growth factor (VEGF) genes. On the other hand, fibrin degradation is mediated primarily by plasmin, which is the active form of the zymogen plasminogen. Conversion of plasminogen to plasmin is under the control of serine protease plasminogen activators, such as the urokinase plasminogen activator (uPA), and their inhibitors, such as the plasminogen activator inhibitor (PAI-1). AIMS: We hypothesized that the deposition of fibrin in the joints may result from an imbalance in the local expression of key genes involved in coagulation and fibrinolytic pathways. To test this hypothesis, we investigated mRNA levels in arthritic versus nonarthritic joint tissues from two murine models of RA: AIA and collagen-induced arthritis (CIA). Genes that are directly implicated in coagulation (TF, TFPI) and fibrinolysis (UPA, PAI1), and other genes that may influence the expression of TF (EGR1, PAR1, VEGF), were investigated using a novel multiprobe RNase protection assay (RPA). Furthermore, we evaluated coagulation activity in arthritic and nonarthritic mice. METHODS: Mice with AIA or CIA were sacrificed at different time points: 2, 4, and 16 h and 3, 7, and 14 d after intra-articular antigen injection for AIA; 42 d after the first immunization for CIA. Total RNA was prepared from arthritic and nonarthritic knees for AIA, or arthritic and nonarthritic hind paws for CIA. Messenger RNA (mRNA) levels of the genes described above were determined by RPA and normalized to glyceraldehyde-3-phosphate dehydrogenase (GAPDH) mRNA levels. Coagulation assays were performed on joint tissue extracts and concentrations of thrombin-antithrombin III (TAT) complex were measured in plasma. RESULTS: In AIA, all the genes studied except VEGF were upmodulated as early as 2 h. PAR1, TFPI, EGR1, and UPA expression decreased to control levels by 16 h, whereas the expression of TF and PAI1 remained elevated. At later times, only TF, PAI1, and UPA showed sustained overexpression. In CIA, gene expression was assayed at only one time point (42 d after immunization) and all genes showed higher mRNA levels in the affected paws than in control paws. In AIA mice, procoagulant activity and TF activity were significantly increased in arthritic joints, and in CIA mice, plasma TAT levels were significantly enhanced. DISCUSSION: Fibrin deposition in synovia is prominent in both RA and experimental arthritis, suggesting that this protein may play a role in the pathogenesis of chronic inflammation. In this study, we have tried to shed some light on the molecular mechanisms leading to extravascular fibrin deposition, using two well-established mouse models of RA: AIA and CIA. The kinetics of gene expression was first analyzed in mice with AIA, because this model allows for an accurate, temporally controlled sampling of synovial inflammation. We then extended our observations by analyzing one time point in CIA, 42 d after immunization, when chronic inflammation is present. We found that in both models, coagulation and fibrinolysis in arthritic joints were significantly increased, and that the most significant increases were in TF and PAI-1. Although the molecular mechanism or mechanisms responsible for the transcriptional changes observed are not completely understood, the increases in TF, PAI-1, and uPA are probably due to the production of proinflammatory cytokines such as IL-1 and TGF-α. These cytokines, whose presence in the inflamed synovium is well documented, are known to induce these genes through the activation of nuclear factor κB (NF-κB), a transcription factor. TF induction is also under the control of a proximal enhancer containing a binding site for the inducible transcription factor EGR1. Indeed, the early rise of EGR1 expression in AIA is consistent with its classification as immediate-early gene and may be responsible for the induction of early expression of TF. Early TF stimulation in AIA can also be accounted for by the transient overexpression of PAR1. Contrary to what has been shown in RA, VEGF expression remained essentially unchanged throughout the progression of AIA, probably reflecting a peculiarity of this murine model. The alteration of the patterns of gene expression was accompanied by increased functional coagulation activity, which was more marked in AIA than in CIA. CONCLUSION: Prominent fibrin deposition in two different animal models of RA – AIA and CIA – can be attributed to modulations in key regulatory genes for coagulation and fibrinolysis.